Retear Rates After Arthroscopic Single-Row, Double-Row, and Suture Bridge Rotator Cuff Repair at a Minimum of 1 Year of Imaging Follow-up: A Systematic Review - Hein, Joel; Reilly, Jordan M; Chae, Jonathan; Maerz, Tristan; Anderson, Kyle (Arthroscopy, 2015)
To determine whether there are differences in retear rates among arthroscopic single-row, double-row, and suture bridge rotator cuff repair. The literature was systematically reviewed for clinical outcome studies assessing arthroscopic single-row, double-row, or suture bridge rotator cuff repair. All included studies indicated the imaging-diagnosed retear rate stratified by preoperative tear size at a minimum of 1 year of follow-up, and retears were diagnosed with either magnetic resonance imaging, ultrasound, or arthrogram. Only studies with comprehensive surgical methods were included, and the repair type was confirmed by the number of rows of fixation and suture configuration. Studies from journals with an impact factor below 1.5 were excluded. Retear rates were grouped and statistically compared using χ(2) tests. Thirty-two studies met the inclusion criteria, yielding a total of 2,048 repairs. Double-row repair (DR) and suture bridge repair (SB) both had significantly lower retear rates than single-row repair (SR) for tears sized 1 to 3 cm (DR, P < .001; SB, P < .001), less than 3 cm (DR, P < .001; SB, P = .004), greater than 3 cm (DR, P = .016; SB, P = .003), and greater than 5 cm (DR, P = .003; SB, P = .003), as well as total retear rates (DR, P = .024; SB, P = .022). DR and SB did not differ significantly from each other in any tear size category. Both DR and SB have lower retear rates than SR in most tear size categories. No differences in retear rates were found between DR and SB. Level IV, systematic review of Level I through IV studies.